Knowledge, attitudes & practices (KAP) on infant & young child feeding (IYCF) of first-time fathers with a child 6-23 months Old - Alincastre, Aaron Joshua C.; Battung, Risha Anne S.; Templonuevo, Charles Bernard R.
The first 1,000 days of a child is a critical phase for optimal growth and development as the brain and body undergo significant development making it particularly vulnerable to the impacts of poor nutrition. As such, it is important to ensure that a child receives adequate nutrition through proper feeding practices. With the changing household dynamics where mothers are also in the workforce, the responsibility of childrearing falls disproportionately on them. Hence, this study investigated the knowledge, attitudes, and practices (KAP) of first-time fathers with a child 6-23 months old on infant and young child feeding (IYCF) and evaluated its effect on the achievement of minimum dietary diversity (MDD) of the child. To test this, a KAP and dietary diversity questionnaire was administered to 50 participants gathered through purposive snowball sampling. Participants’ knowledge was found to have very poor (n = 1), good (n = 24), to very good (n = 25), attitude was very poor (n = 1), good (n = 10), to very good (n = 39), while practice was very poor (n = 1), average (n = 4), good (n = 19) to very good (n = 26). Thirty-five (n = 35) was found to meet minimum dietary diversity among participants’ children. Knowledge and attitude was found to have a moderately positive correlation (τ = 0.6166, α = 6.197e-08), attitude was found to have a weak positive correlation with practice (τ = 0.3752, α = 0.000808), while practice and knowledge had a moderate positive correlation (τ = 0.4572, α = 8.528e-06). These findings imply that improving the knowledge on IYCF of a father may improve attitude and practice and vice versa. Knowledge (τ = 0.1128) and practice (τ = 0.2016) was found to be weakly positively correlated with the achievement of MDD while attitude (τ = 0.0656) was found to have a negligible correlation. However, the association of KAP and MDD was not statistically significant at α = 0.3761, α = 0.6366, α = 0.1068 respectively. Further studies are recomme